Identification of human papillomavirus as a preventive strategy for cervical cancer in asymptomatic women in the Peruvian Andes - Silva-Caso, Wilmer (2014)
Objective: To detect the most prevalent human papillomavirus (HPV) genotypes samples of asymptomatic Peruvian women by analyzing the correlation betwe ienn c Pearvpiacnailc somlaeoaur (PAP)-stained cervical tests and PCR-sequencing. Methods: A total of 254 women attending routine gynecological examinations were included in pthaitsh ostluogdiys.t Tahned scalmaspsliefise dw ebrye tahnea Blyeztehde sbdya PsAysPt etmec.h HnPiqVu ea manpdli feicxaatmioinn ewda su nddoenre au msinicgr othsceo pprei mbeyr as specific for E1 region and positive specimens were confirmed by direct sequencing. Results: The prevalence of HPV was investigated in 254 cervical scrape samples by PCR. PAP smear showed that 94.9% cases had normal morphology and 5.1% had an inflammatory pattern; 2p0r.e5v%a lwenert eg efonuontydp teo ibne c ionrfreeclatetido nw iwthit hH PchVa, ncgoems pinri scienrgv i2c0a dl icfyfetorelongt yg.enotypes. HPV16 was the most Conclusions: Our results suggest the HPV is very frequent even in women with negative PAP, eannddo PceCrRvi csaele smasm tpol ebs.e Itdheen tbifeicsat toiopnt ioofn t htoe HdePtVe rgmeinnoety tphee inc aaussyamtipvteo magateinc tw oofm HePnV m ianyf eaclltoiown t hine nimatpulreaml henisttaotriyo no fo tfh ea pdpisroepasreia aten dp rthope hsyulbascetqicu emnet adseuvreelso pwmheicnht omf acye rhviacvael ma adliirgencatn icmy.pact